Health-risk behaviors among Iranian university students, 2019: a web-based survey - Farhad Shekari; Peyman Habibi; Haidar Nadrian; Asghar Mohammadpoorasl (BMC, 2020)
Abstract Background High-risk behaviors are among the most serious threats for the physical and mental health of adolescents and young adults. Our aims in this study were to investigate the subgroups of students based on risky behaviors and to identify the prevalence rate of these subgroups. Methods This cross-sectional web-based survey was conducted from July to August 2019 in Tabriz, Iran. We performed proportional sampling in all nine universities of the city, according to the number of students in each university. Applying an online survey questionnaire, the data were collected from 3649 students and analyzed using Latent Class Analysis. Results For total sample, standardized prevalence rates of cigarette smoking, hookah use, alcohol consumption, substance abuse and unsafe sex were 18.5 (Confidence Interval (CI) 95%: 17.3-19.8), 9.1 (CI 95%: 8.2-10.1), 9.2 (CI 95%: 8.3-10.2), 8.3 (CI 95%: 7.4-9.3) and 14.5 (CI 95%: 13.3-15.7), respectively. Three latent classes of risky behaviors were determined among students: a) low risk b) smoking and c) high risk. About 18% of boys and 1.5% of girls were in the high risk class. Cigarette smoking (18.5%, CI 95%: 17.3-19.8) and substance abuse (8.3%, CI 95%: 7.4-9.3) were the most and the least common risky behaviors among the students. Conclusion In this we-based survey, a considerable number of students, particularly boys (18%), was at high-risk class, stressing the need for preventive interventions for this group of youth. Our findings are beneficial for planning and development of risky-behavior preventive strategies to prevent high-risk behaviors among college students.